Not just the usual suspects: insect herbivore populations and communities are associated with multiple plant nutrients - Joern, Anthony; Provin, Tony; Behmer, Spencer T. (My University, 2012)
The relationship between plant nutrient content and insect herbivore populations and community structure has long interested ecologists. Insect herbivores require multiple nutrients, but ecologists have focused mostly on nitrogen (an estimate of plant protein content), and more recently phosphorus (P); other nutrients have received little attention. Here we document nutrient variation in grass and forb samples from grassland habitats in central Nebraska using an elemental approach; in total we measured foliar concentrations of 12 elements (N and P, plus S, B, Ca, Mg, Na, K, Zn, Fe, Mn, and Cu). We detected significant variability among sites for N, P, Mg, Na, K, and Cu. We next used a model selection approach to explore how this nutritional variation and plant biomass correlate with grasshopper densities (collectively and at the feeding-guild level), and principal component analysis to explore nutrient correlations with grasshopper community species composition. When all grasshoppers were pooled, densities varied among sites, but only P was associated with abundance of the elements shown to vary between sites. Different responses occurred at the feeding-guild level. For grass specialists, densities were associated with N, plus P, Mg, and Na. For forb specialists, N and P were often associated with density, but associations with Na and K were also observed. Finally, mixed-feeder abundance was strongly associated with biomass, and to a lesser extent P, Mg, Na, and Cu. At the community level, B, Ca, Zn, and Cu, plus biomass, explained >30% of species composition variation. Our results confirm the positive association of N and P with insect herbivore populations, while suggesting a potential role for Mg, Na, and K. They also demonstrate the importance of exploring effects at the feeding-guild level. We hope our data motivate ecologists to think beyond N and P when considering plant nutrient effects on insect herbivores, and make a call for studies to examine functional responses of insect herbivores to dietary manipulation of Mg, Na, and K. Finally, our results demonstrate correlations between variation in nutrients and species assemblages, but factors not linked to plant nutrient quality or biomass likely explain most of the observed variation.
Keywords: Acrididae; Grasshoppers; Insect herbivory; Mixed grass prairie; Nebraska sandhills grassland (USA); Nutritional ecology; Orthoptera; Physiological ecology